A new standardized clinical‐grade protocol for banking human umbilical cord tissue cells. Issue 12 (9th September 2015) - Fazzina, Raffaella; Mariotti, Andrea; Procoli, Annabella; Fioravanti, Daniela; Iudicone, Paola; Scambia, Giovanni; Pierelli, Luca; Bonanno, Giuseppina
Abstract : BACKGROUND: Mesenchymal stromal cells (MSCs) isolated from human umbilical cord tissue (UCT) can be considered the perfect candidates for cell‐based therapies and regenerative medicine. UCT‐derived MSCs can be cryogenically stored in cell banks and expanded as needed for therapeutic uses. STUDY DESIGN AND METHODS: We developed a new method for UCT‐MSC isolation, cryopreservation, and expansion, following all criteria required by a stem cell bank. UCT‐MSCs were isolated either by manual dissociation (MM) or by a semiautomatic dissociation system (SAM). In both protocols UCTs were treated enzymatically using Type IV collagenase good manufacturing practices (GMP) graded and hyaluronidase (medicinal product). Isolated UCT‐MSCs were cryopreserved and analyzed after thawing for phenotype; for proliferation rate; and for their osteogenic, adipogenic, and chondrogenic differentiation capabilities. RESULTS: We found that SAM reduced the time of tissue enzyme exposure and enabled us to obtain a homogeneous single‐cell suspension deprived of tissue fragments. The isolated cells in both groups showed high expression of MSC markers CD105, CD73, and CD90 and similar differentiation capabilities, phenotype, and proliferation potential. Moreover, the final yield of MSCs was comparable between the two techniques. CONCLUSION: In this study, we have established a reliable and standardized protocol to isolate UCT‐MSCs from UCT for cell banking purposes. Processing the whole umbilical tissue with GMP‐graded enzymes using a semiautomatic dissociator allowed us to obtain a single‐cell suspension product with a known number of isolated cells that can be cryopreserved right after isolation and thawed as needed for expansion and clinical use.